When SARS‐CoV‐2 comes knocking on your lab door: Individual scientists’ experiences during the pandemic - Wolinsky, Howard (EMBO Rep, 2020)
A snapshot of how scientists are personally affected by the global Covid‐19 pandemic.[Image: see text]